Dialectal Speech and Standard Language: Aspect of Code Alteration - Aliūkaitė, Daiva (Kalbotyra, 2006)
The present article discusses the choice between dialectal speech and standard language on the basis of theory of identity and linguistic identity, the sociolinguistic concept of code alteration and the understanding of language power. The article formulates a hypothesis of four statements that the selection of the dialectal code may be imposed by the identification of an individual with some group, the power of other participants of the discourse, the communicative discourse and its inertness as well as the indifference of the discourse participants to the way of interlocution. The main analytical part of the article is structured by the four statements of the hypothesis. Each statement is grounded both by the data of a sociolinguistic test, i.e. by the respondents’ reactions to the data of a perceptive questionnaire and by insights and conclusions of foreign explorers performed either in the past or currently. The article distinguishes between natural, provoked and stylized alterations of standard language and dialectal speech which is grounded both by exploration of empirical data and by theoretical statements of sociolinguistic and perceptive dialectology.